31.4k views
0 votes
Which property of exponents must be used first to solve this expression? (iy2)1/3

User Cory Silva
by
5.2k points

1 Answer

3 votes

Explanation:

"must be used first" is a very hard phrasing. multiplication is commutative.

and I am not sure that the problem is stated correctly.

I read here

(i×y²) to the power of 1/3.

i is the imaginary constant sqrt(-1) ?

exponents brought themselves to the power of something else multiply.

e.g.


({2}^(3))^(4) = {2}^(12)

exponents in multimedia expressions of the same base simply add up.

e.g.


{2}^(3) * {2}^(4) = {2}^(7)

a negative exponent means that the expression with the same positive exponent is just at the bottom of a division.

e.g.


{2}^( - 3) = 1 / {2}^(3)

and a fraction as exponent specifies a root to be taken.

e.g


{2}^(1 / 3) = \sqrt[3]{2}

so, I would do all the exponent multiplications to simplify the expression.


\sqrt[3]{i * {y}^(2) } = ({i * {y}^(2) })^(1 / 3) =


= ( { - 1}^(1 / 2) * {y}^(2) ) ^(1 / 3)

1/2 × 1/3 = 1/6

2 × 1/3 = 2/3


= { - 1}^(1 / 6) * {y}^(2 / 3) = \sqrt[6]{ - 1} * \sqrt[3]{ {y}^(2) }

so, as we can see, we can move freely from multiplying the fraction exponents to converting them into root expressions and vice versa.

User Joyrex
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.